Saving and current account in the context of shari‘ah contract - abdul azeez bello, Shafii; Hassan, Rusni (OMICS International Journal, 2014)
Islamic banking is a new phenomenon that has taken many observers by surprise. There are three types of account which are commonly known in the Islamic Banks. These are: Current Account, Saving Account and Investment account. Moreover, this paper proposed to analysis the Savings and Current Account Deposit in the context of Shari‘ah contract. The Shari‘ah principles applicable to saving account are Al-Wadi‘ah, Mudarabah and Al-Qard Hassan. However, Al- Qard is commonly offered by Islamic banks in the Middle East. The Shari‘ah compliant of current account based on the Al-Wadi‘ah Yad Dhamanah (safe custody) principle which refers to a contract between the owner of funds (account holder) and the bank for safe keeping purposes. This paper claims that deposits from savers are an important source of financial strength for the Islamic banks. They use it to increase their capacity for financing operations and thereby increase profit for the shareholders. In addition, it argued that gifts in wadi‘ah and qard hassan allowed because the excess or expected return is not contractual in nature and the bank is under no obligation to provide a return and return is purely in the nature of gift, whereby, gifts by definition do not constitute ribā.